2018
DOI: 10.1080/21505594.2018.1511677
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the original Elberg Brucella melitensis Rev.1 vaccine strain reveals insights into virulence attenuation

Abstract: The live attenuated Brucella melitensis Rev.1 Elberg-originated vaccine strain has been widely used to control brucellosis in small ruminants. However, despite extensive research, the molecular mechanisms underlying the attenuation of this strain are still unknown. In the current study, we conducted a comprehensive comparative analysis of the whole-genome sequence of Rev.1 against that of the virulent reference strain, B. melitensis 16M. This analysis revealed five regions of insertion and three regions of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…On this basis, the high attenuation of Rev1 wzm should have led to failed efficacy; however, and, unpredictably, Rev1 wzm (but not Rev1 wzt) triggered a splenomegaly associated with a particular Th1 cytokine balance, as well as to a protective efficacy against virulent challenges. Besides the genetic and phenotypic divergences described between the Rev1 and 16M parentals related to virulence attenuation (Issa and Ashhab, 2016;Salmon-Divon et al, 2018Kornspan et al, 2020), we have now described additional differences in genetic transcription, antigenicity evidenced by Western blot, and susceptibility to antibiotics and environmental stress factors. Indeed, when wzm/wzt mutations were applied to other brucellae (Wang et al, 2014a;Grilló et al, 2017;Aragón-Aranda et al, 2020;Lalsiamthara et al, 2020), neither mutant was as immunogenic as Rev1 wzm.…”
Section: The Impact Of the Rev1 Background On Rev1 Wzm Vaccine Proper...mentioning
confidence: 69%
“…On this basis, the high attenuation of Rev1 wzm should have led to failed efficacy; however, and, unpredictably, Rev1 wzm (but not Rev1 wzt) triggered a splenomegaly associated with a particular Th1 cytokine balance, as well as to a protective efficacy against virulent challenges. Besides the genetic and phenotypic divergences described between the Rev1 and 16M parentals related to virulence attenuation (Issa and Ashhab, 2016;Salmon-Divon et al, 2018Kornspan et al, 2020), we have now described additional differences in genetic transcription, antigenicity evidenced by Western blot, and susceptibility to antibiotics and environmental stress factors. Indeed, when wzm/wzt mutations were applied to other brucellae (Wang et al, 2014a;Grilló et al, 2017;Aragón-Aranda et al, 2020;Lalsiamthara et al, 2020), neither mutant was as immunogenic as Rev1 wzm.…”
Section: The Impact Of the Rev1 Background On Rev1 Wzm Vaccine Proper...mentioning
confidence: 69%
“…CIIMS-BH-2 and CIIMS-NV-1 had non-synonymous mutation in lysE type translocator family protein. It was reported that B. melitensis Rev.1 had a mutation in lysE type translocator family protein when compared with 16M strain ( Salmon-Divon et al, 2018 ).…”
Section: Core and Accessory Gene Compositionsmentioning
confidence: 99%
“…Filtered SNPs were subjected to annotation by the SnpEff tool v4.3T [53]. The SnpEff database of the 16 M genome (2002 assembly; [54] and the Rev.1 genome (2018 assembly; [55,56] were built based on GenBank files that were downloaded from NCBI. To validate the detected SNPs and to detect additional mutations that were missed, the analysis was repeated using alignment against the 16M reference genome followed by SNP calling.…”
Section: Snp Detectionmentioning
confidence: 99%